Case report: Advice for schools on managing functional tic-like behaviours - Owen, Tamsin; Silva, Juliana; Grose, Claire; Bailey, Alice; Robinson, Sally; Anderson, Seonaid; Ludlow, Amanda; Sharp, Sarah; Toghill, Lucy; Hedderly, Tammy (Frontiers in Psychiatry, 2022)
There has been an increase in the occurrence of sudden onset functional tic-like behaviours in adolescents during the COVID-19 pandemic, which has had a significant impact on the affected individual’s ability to engage with education. The aim of this article is to generate discussion and inform practice within schools with regard to the management of functional tic-like behaviours. An advice sheet for schools has been produced based on clinical expertise and experience of consulting with schools around the management within education settings. Case examples are presented highlighting the importance and impact of these strategies. We also highlight the need for further evaluation of the effectiveness of the advice sheet in collaboration with schools and families.